STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWI DI SMK UNGGULAN AN-NUR BULULAWANG MALANG - Nhaswa Nabilatul Mufida; Abdulloh (Journal of Practice Learning and Educational Development, 2025)
This study aims to describe the strategies used by Islamic Religious Education (PAI) teachers to increase student motivation at the An-Nur Bululawang Vocational High School in Malang. The background of this research stems from the low learning motivation of some students in PAI lessons, characterized by a lack of active engagement and enthusiasm for learning in class. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that teachers implemented various strategies, such as varied learning methods (discussions, interactive lectures, educational games), affective approaches, the use of digital media, and the provision of educational rewards and punishments to build learning motivation. Supporting factors for these strategies include teacher pedagogical competence, adequate learning resources, and a religious environment at the Islamic boarding school. Meanwhile, obstacles encountered included varying levels of student motivation, a lack of teacher training in innovative approaches, and a high administrative burden. In conclusion, responsive, communicative, and contextual teacher strategies can foster a more meaningful learning environment and significantly increase student motivation.